Artemis: realidade aumenta e gamificação para ensino de arquitetura de computadores com mips - Silva, Geofrangite Câmara da (Universidade Federal Rural do Semi-Árido, 2019)
Simulators are tools developed to increase the level of content abstraction. They have been of great importance in the courses of computer science for the teaching of contents of disciplines that deal with the hardware, considered as complex in terms of learning. In the context of Organization and Computer Architecture several simulators have been and continue to be developed, however, do not present integration with the study material (book). This work presents a simulator of the architecture of the MIPS processor that aims to allow greater integration between the study material and the tools to support learning. For this, the developed simulator recognizes, through augmented reality, the figures the figures in Patterson and Hennessy's book "Computer Organization and Design", 3ed and recreates them as interactive models with which it is possible to interact to facilitate learning by obtaining information and visualization of the internal workings of MIPS. A methodology of use based on gamification is also proposed. A validation was performed in which it was verified that the simulator is able to promote improvement in students' performance. In addition, the validation participants considered it very useful to assist in the learning of OCA, felt that they had learned a lot using it and considered it important to include RA and gamification to stimulate learning
Keywords: Realidade aumentada; Gamificação; Arquitetura de computadores; MIPS; Computação e educação; Ferramenta educacional; Augmented reality; Gamification; Computer architecture; MIPS; Computing and education; Educational tool; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO